2015
DOI: 10.1182/blood-2015-03-636548
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib combined with multiagent chemotherapy for newly diagnosed Philadelphia-positive acute lymphoblastic leukemia

Abstract: Key Points• Nilotinib plus multiagent chemotherapy was feasible and showed a comparable outcome to previous results with imatinib for Ph-pos ALL.• The achievement of deep MR with nilotinib at postremission correlated well with the clinical outcomes for Ph-pos ALL.We investigated the effects of nilotinib plus multiagent chemotherapy, followed by consolidation/maintenance or allogeneic hematopoietic cell transplantation (allo-HCT) for adult patients with newly diagnosed Philadelphia-positive (Ph-pos) acute lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(130 citation statements)
references
References 31 publications
6
121
0
3
Order By: Relevance
“…49 Both dasatinib and nilotinib have been used in combination with chemotherapy for the front-line treatment of de novo Ph + ALL. 18,20,50 Prior to the advent of TKIs, combination chemotherapy regimens were not durable. Myeloablative ASCT was considered to be the only curative option and was offered to all patients with Ph + ALL in first CR who had a suitable donor.…”
Section: Discussionmentioning
confidence: 99%
“…49 Both dasatinib and nilotinib have been used in combination with chemotherapy for the front-line treatment of de novo Ph + ALL. 18,20,50 Prior to the advent of TKIs, combination chemotherapy regimens were not durable. Myeloablative ASCT was considered to be the only curative option and was offered to all patients with Ph + ALL in first CR who had a suitable donor.…”
Section: Discussionmentioning
confidence: 99%
“…In the de novo study, induction with nilotinib plus chemotherapy was given to 50 patients with Ph+ all. Results demonstrated a cr rate of 90%, with an os rate of 66% at 2 years 79 . In one study in the relapsed setting, a partial response of 10% was found 31 .…”
Section: 23mentioning
confidence: 95%
“…Nilotinib: Three studies in a total of 70 patients examined the efficacy of nilotinib: one in de novo patients and two in relapsed patients 31,45,79 . In the de novo study, induction with nilotinib plus chemotherapy was given to 50 patients with Ph+ all.…”
Section: 23mentioning
confidence: 99%
See 2 more Smart Citations